AVALIAÇÃO DAS ALTERAÇÕES NA SOBREMORDIDA E NAS ALTURAS FACIAIS ANTERIOR E POSTERIOR, DECORRENTES DO TRATAMENTO ORTODÔNTICO COM EXTRAÇÃO DE PRÉ-MOLARES, EM PACIENTES COM DIFERENTES TIPOS FACIAIS. - Fagundes, Adriana Lessa Fadel (2008)
The present study has investigated the changes in overbite and lower anterior facial heights for patients with Class I malocclusion and different facial types with teeth crowd, which were submitted to four premolar extractions, on the pre and post orthodontic treatment. Lateral cephalograms of 36 individuals aging from 12 years and 2 months to 16 years and 5 months, who were treated with Straight Wire mechanics, were selected. For analysis purpose, AFA, AFAI, AFP, FMA, SN.GoGn measures, other than linear measures described by Hans et al, were utilized. Changes in anterior and posterior facial heights were similar for all three studied groups and increased at the end of the orthodontic treatment without, however, statistical significance in the anterior facial height for the hypodivergent group. FMA showed statistically significant changes just for hypodivergent while Sn.GoGn showed them for both hypo and hyperdivergent groups. Regarding the Hans linear measures, a statistically significant increase for the hypodivergent group was observed in TLI and MNSK; for the mesofaciais group, the same has occurred in BUI and MNSK, and for the dolicofaciais group, all measures but TUI showed significant increase. In all studied groups, a reduction in overbite was observed.(AU)